DEFORMASI LANDFORM PASCAGEMPA TEKTONIK JOGJAKARTA 27 MEI 2006 - Santoso Santoso (Jurnal Geologi dan Sumberdaya Mineral, 2007)
The tectonic earthquake of Jogjakarta 2 7 Mei 2006 caused damages and more than 6000 people died.  The damage include houses, office buildings, public service, and other infrastructure.   On the other hand, the earthquake causes landform deformation along the Opak fault Zone and Patuk  fault  Zone, such as land crack, rock slide/fall, and liquefaction in a dug well.                                                                                                                                                                  Based on field identification of the landform deformation and damage pattern, two imaginary lines namely Opak fault Zone and Patuk fault Zone can be traced. Opak fault Strip elongates from end of the Opal River to Prambanan with general direction NW-SE,  while the Patuk fault Strip elongates from Parangtritis-Patuk to Gantiwamo/Wedi,  Klaten Regency with direction N40-450E. Keywords: landform deformation, earthquake